2006
DOI: 10.1207/s15548430jlr3803_3
|View full text |Cite
|
Sign up to set email alerts
|

Looking Backward: Reflections on a Career in Reading

Abstract: When I agreed to do an article that would capture the essence of my research, I did not realize how hard it would be. What made the task difficult was that I was not sure how to write the article in an interesting way. I thought a descriptive narrative of my work might be about as interesting as reading the phone directory. As I considered this problem, I realized that a presentation of my work against the backdrop of the history of reading and writing might be appealing. This history could take the long view … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 8 publications
1
32
0
8
Order By: Relevance
“…Giving continued practice and successive exposure to the targeted tasks (Samuels, 2006) in the study lead to automaticity and fluency in the results. By giving explicit FTA instruction to the students we gave them the opportunity to practice them to become automatic (Kuhn & Stahl, 2003;Rasinski, 2006).…”
Section: Theory and Practice In Language Studies 939mentioning
confidence: 91%
See 1 more Smart Citation
“…Giving continued practice and successive exposure to the targeted tasks (Samuels, 2006) in the study lead to automaticity and fluency in the results. By giving explicit FTA instruction to the students we gave them the opportunity to practice them to become automatic (Kuhn & Stahl, 2003;Rasinski, 2006).…”
Section: Theory and Practice In Language Studies 939mentioning
confidence: 91%
“…Additionally, explicit instruction may eventually lead to more learner automaticity and fluency. Current studies show that automaticity and fluency is the by-product of continued practice and successive exposure to the targeted tasks (Samuels, 2006). Differently stated, students should be given multiple opportunities to practice the assigned activities…”
Section: Introductionmentioning
confidence: 99%
“…The research also demonstrated that scholars have some differing views on the exact ways that fluency develops (Rasinski, 2012;Samuels, 2006;Hudson et al, 2009; Nichol et al, 2012).…”
mentioning
confidence: 92%
“…Researchers believed that fluency plays a critical role as the bridge or gateway that allows student to make meaning (Gorsuch & Taguchi, 2010;Rasinski, 2012). The research also demonstrated that scholars have some differing views on the exact ways that fluency develops (Rasinski, 2012;Samuels, 2006;Hudson et al, 2009; Nichol et al, 2012).Some asserted a bottom-up view, while others chose a top-down view. In the predominant view, however, readers must attain automaticity at the word recognition level in order to free cognitive resources for comprehension (Rasinski, 2012;Samuels, 2006).…”
mentioning
confidence: 98%
See 1 more Smart Citation